Reframing the narrative: Renewing power resources and capabilities in union campaigns for public education. (November 2021) - Gavin, Mihajla
Neoliberal logics have put teacher unions on the defensive, requiring evaluation of the resources and capabilities necessary to improve teachers' industrial and professional conditions and broader public education issues. This article examines the case of a teachers' union in Australia – the NSW Teachers' Federation – and their renewal of resources and capabilities in recent public education campaigns. In applying a power resources and capabilities framework to the analysis of two prominent campaigns, this article develops the argument for renewal of power resources and capabilities through mobilising and transforming narrative resources and reframing public education issues in order to challenge ideological narratives around public education, build discursive power and sustain influence within a neoliberal environment.